2012
DOI: 10.1177/0266242612437560
|View full text |Cite
|
Sign up to set email alerts
|

Is entrepreneurship a leading or lagging indicator of the business cycle? Evidence from UK self-employment data

Abstract: Previous studies provide suggestive evidence that entrepreneurship varies with the state of the business cycle. This article extends the knowledge base by exploring whether the rate of selfemployment -a widely used measure of entrepreneurship -is a lagging or leading indicator of the business cycle. The study, which utilizes time series UK data on aggregate output, unemployment and self-employment rates, is robust to structural breaks in the cyclical relationships between these variables. The study finds evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 49 publications
3
52
0
3
Order By: Relevance
“…This represents the loss of three years of trend-level economic growth for the UK economy. At a time when larger businesses shed vast numbers of employees and unemployment rose by 674,000, policymakers increasingly looked to small and medium-sized enterprises (SMEs) to provide new employment opportunities and help drag the economy out of recession (Department for Business, Innovation and Skills, 2013), the implicit assumption being that: (a) SMEs are more flexible and resilient (Bednarzik, 2000;Binks and Jennings, 1986;Smallbone et al, 2012aSmallbone et al, , 2012b; (b) SMEs are more labour-intensive (Cowling, 2003;Robbins et al, 2000); and (c) that periods of disequilibrium create new opportunities for entrepreneurs (Parker et al, 2012;Schumpeter, 1942). Yet even if we generally believe that SME's in the economy are more dynamic and opportunistic than large firms, SMEs are not immune to large contractions in the demand for goods and services.…”
Section: Introductionmentioning
confidence: 99%
“…This represents the loss of three years of trend-level economic growth for the UK economy. At a time when larger businesses shed vast numbers of employees and unemployment rose by 674,000, policymakers increasingly looked to small and medium-sized enterprises (SMEs) to provide new employment opportunities and help drag the economy out of recession (Department for Business, Innovation and Skills, 2013), the implicit assumption being that: (a) SMEs are more flexible and resilient (Bednarzik, 2000;Binks and Jennings, 1986;Smallbone et al, 2012aSmallbone et al, , 2012b; (b) SMEs are more labour-intensive (Cowling, 2003;Robbins et al, 2000); and (c) that periods of disequilibrium create new opportunities for entrepreneurs (Parker et al, 2012;Schumpeter, 1942). Yet even if we generally believe that SME's in the economy are more dynamic and opportunistic than large firms, SMEs are not immune to large contractions in the demand for goods and services.…”
Section: Introductionmentioning
confidence: 99%
“…One of few exceptions is Parker et al (2012). Their study showed no straightforward relationship between entrepreneurship and economic change.…”
Section: Previous Empirical Researchmentioning
confidence: 96%
“…Distinct sub-periods could also be identified. Parker et al (2012) found apparent structural breaks in these causal relationships. The four distinct sub-periods identified displayed different cyclical relationships.…”
Section: Previous Empirical Researchmentioning
confidence: 98%
“…In fact, the relationship between the economic cycle and entrepreneurship is difficult to understand as a consequence of the bi-directional causality. In other words, entrepreneurship both causes and is caused by the economic cycle (Parker et al 2012). For the case of Spain, Verheul et al (2006) state that the quantity of business ownership does not contribute to reduce unemployment, suggesting that it is its quality what helps to decrease it.…”
Section: Determinants Of Job Satisfaction: 2006-2010mentioning
confidence: 99%